Polymicrobial antibiofilm activity of the membranotropic peptide gH625 and its analogue. (December 2018) - de Alteriis, E.; Lombardi, L.; Falanga, A.; Napolano, M.; Galdiero, S.; Siciliano, A.; Carotenuto, R.; Guida, M.; Galdiero, E.
Abstract: This work illustrates a new role for the membranotropic peptide gH625 and its derivative gH625-GCGKKK in impairing formation of polymicrobial biofilms. Mixed biofilms composed of Candida and bacterial species cause frequently infections and failure of medical silicone devices and also show a major drug resistance than single-species biofilms. Inhibition and eradication of biofilms were evaluated by complementary methods: XTT-reduction, and crystal violet staining (CV). Our results indicate that gH625-GCGKKKK, better than the native peptide, strongly inhibited formation of mixed biofilms of clinical isolates of C. tropicalis/S. marcescens and C. tropicalis/S. aureus and reduced the biofilm architecture, interfering with cell adhesion and polymeric matrix, as well as eradicated the long-term polymicrobial biofilms on silicone surface. Highlights: Polymicrobial biofilms cause frequently infections. The use of antimicrobial peptides represents a possible strategy to treat biofilms. Membranotropic gH625 peptide and its analogue are effective against polymicrobial biofilms.